Development of a CFD model for simulating vehicle cabin indoor air quality. (July 2018) - Chang, Tong-Bou; Sheu, Jer-Jia; Huang, Jhong-Wei; Lin, Yu-Sheng; Chang, Che-Cheng
Graphical abstract: Highlights: This study has performed CFD simulations to examine the CO2 concentration in the cabin of a typical passenger vehicle. The minimum outdoor air supply rate required to achieve a CO2 concentration of 1000 ppm in the cabin is 9.2 l/s per occupant. For a CO2 concentration criterion of 2000 ppm, the required outdoor fresh air flow rate reduces to 3.6 l/s per occupant. Abstract: As the level of CO 2 within the vehicle cabin increases, the risk of accidents as a result of driver drowsiness and a slowing of the reactions also increases. Accordingly, a CFD simulation model was developed in this study to explore the effects of outdoor air ventilation rate on vehicle cabin indoor air quality and the amount of outdoor air required for each person in a vehicle. The results show that using the outdoor air supply rate recommendations of ASHRAE Standard 62.1 (i.e. 2.5 l/s per person) the mean CO2 concentrations in the cabin are around 2850 ppm. The results also show that using the outdoor air supply rate recommendations of 4.0 l/s per person for improved human wellbeing, the corresponding mean CO2 concentrations in the cabin are around 1810 ppm. Moreover, the present study found that an outdoor fresh air flow rate of 9.2 l/s per passenger was sufficient to reduce the carbon dioxide concentration within the cabin to a safe value of 1000 ppm. Furthermore, an outdoor fresh air flow rate of 3.6 l/s per passenger resulted in a carbon dioxide concentration of around 2000 ppm.